Interaction between specific fatty acids, GLP-1 and insulin secretion in humans. - Beysen, C; Karpe, F; Fielding, B; Clark, A; Levy, J; Frayn, K (2002)
AIMS/HYPOTHESIS: Fatty acids affect insulin secretion in vivo, but little is known about the effects of specific fatty acids. Our aim was to investigate differential effects of acutely increased plasma monounsaturated, polyunsaturated and saturated fatty acids on glucose-stimulated insulin secretion in healthy humans. METHODS: A new experimental protocol was used to increase plasma monounsaturated (MUFA test), polyunsaturated (PUFA test) or saturated (SFA test) non-esterified fatty acids for 2 h by repeated oral fat feeding and continuous intravenous heparin infusion. This was followed by a hyperglycaemic clamp (10 mmol/l) to test insulin secretion in response to a prior plasma NEFA increase. RESULTS: Total plasma NEFA concentrations were increased during the fat tests compared to the control visit (1.7-fold increase for MUFA and SFA tests and 1.4-fold increase for PUFA test; p<0.001). Exaggerated responses in plasma insulin, C-peptide and proinsulin concentrations were seen during the hyperglycaemic clamp after increasing plasma NEFA concentrations compared with the control (p<0.01). The effects were greatest for the MUFA test followed by the PUFA test and SFA test (p<0.01). Plasma GLP-1 concentrations increased during fat feeding, with a higher response during the MUFA test compared to PUFA and SFA tests (p<0.01). CONCLUSION/INTERPRETATION: Increasing plasma NEFA concentrations by oral fat feeding with heparin infusion augments glucose-stimulated insulin secretion with the greatest effect for monounsaturated fatty acids and the lowest effect for saturated fatty acids. Monounsaturated fatty acids also increase GLP-1 more than saturated fatty acids. Therefore, the exaggerated insulin concentrations could be due to both NEFA and GLP-1.